Literature Review: Group Counseling with Transactional Analysis Approach to Overcome Aggressiveness - Maya Selvia; Silvianetri Silvianetri (Jurnal Counseling Care, 2025)
This study aims to analyze the effectiveness of Group Counseling with a Transactional Analysis approach in overcoming aggressive behavior. The type of research used is library research, namely by reviewing and analyzing various relevant literature related to the topic of discussion. Transactional Analysis is an approach to counseling that emphasizes communication patterns between individuals as a reflection of a person's psychological condition. This approach is considered appropriate for group counseling because group dynamics provide space for individuals to interact and improve unhealthy transactional patterns. In this context, the form and method of communication displayed by group members are the main indicators for identifying and dealing with problems that arise, including aggressive behavior. Aggression itself is an individual's drive or tendency to hurt others, either physically, verbally, or psychologically. Through Transactional Analysis-based group counseling, individuals can be invited to recognize dominant ego states, manage emotions, and build healthier and more constructive communication. The results of the study indicate that this approach has great potential in helping individuals reduce aggressive behavior by increasing self-awareness and interpersonal skills. Keywords: Group Counseling, aggressive behavior, Transactional Analysis.